Production of eco-efficient earth-based plasters - Santos, Tânia (2022)
This work was supported by Fundação para a Ciência e a Tecnologia (FCT) under DB-HERITAGE project (PTDC/EPH-PAT/4684/2014). The authors also acknowledge the EMBARRO Company for supplying the majority of the mortar materials and are grateful to Antonio Santos Silva, Miguel Teixeira, Sandra Noivo, Teresa Gonçalves and Vitor Silva for the support throughout the testing campaign. The support of COST Actions FP1303 “Performance of biobased building materials” and RILEM Technical Committees TCE, “Testing and Characterisation of Earth-based building materials and elements” and HDB, “Hygrothermal behaviour and Durability of Bio-aggregate based building materials”, are also acknowledged.